Penerapan Backward Design Model Dalam Matakuliah Basic Science Untuk Meningkatkan Literasi Guna Membangun Wawasan Kristen Alkitabiah - Kurniawati Martha (SANCTUM DOMINE: JURNAL TEOLOGI, 2021)
Technology helps us to get information in a short time. With an internet connection, we can easily get any information. But there is an emergency literacy problem in Indonesia. The question that arises in the minds of researcher is, "How could this happen, a country with 2nd largest number of libraries in the world experiencing a literacy emergency?" However, it turns out that what is meant by literacy is more than just reading and writing. Literacy is the ability to interpret information critically so that everyone can access science and technology as an effort to improve the quality of life. Therefore, it must be realized the importance of the role of Christian educators in contributing to improving students’ literacy skills in order to build an understanding of the biblical worldview. The researcher tries to use the Back Design Model to improve students' literacy skill. The research method is descriptive qualitative method. Subjects were students from Christian Religious Education and Social Sciences study programs in the Basic Science courses. The researcher applies the Backward Design Model with the stages: Determining Learning Goals and Targets (determining objectives), Assessment Planning and Learning Activity Planning. These stages are proven to be able to improve the literacy skills of students who take Basic Sciences courses, namely in increasing reading interest, giving awareness to students to choose unreliable sources and honing students' abilities to criticize problems assigned by lecturers on the basis of on biblical Christian worldview.